2013
DOI: 10.1002/jbm.a.34929
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the hydration on the biomechanical properties in a fibrin‐agarose tissue‐like model

Abstract: The effect of hydration on the biomechanical properties of fibrin and fibrin-agarose (FA) tissue-like hydrogels is reported. Native hydrogels with approximately 99.5% of water content and hydrogels with water content reduced until 90% and 80% by means of plastic compression (nanostructuration) were generated. The biomechanical properties of the hydrogels were investigated by tensile, compressive, and shear tests. Experimental results indicate that nanostructuration enhances the biomechanical properties of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
91
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 75 publications
(104 citation statements)
references
References 29 publications
11
91
0
2
Order By: Relevance
“…In fact, fibrin‐agarose biomaterials demonstrated to be safe and biocompatible in relevant animal models . In addition, several previous works demonstrated that fibrin‐agarose biomaterials could have appropriate biomechanical properties allowing future clinical use . However, these biomaterials had not been associated to surgical meshes before.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, fibrin‐agarose biomaterials demonstrated to be safe and biocompatible in relevant animal models . In addition, several previous works demonstrated that fibrin‐agarose biomaterials could have appropriate biomechanical properties allowing future clinical use . However, these biomaterials had not been associated to surgical meshes before.…”
Section: Discussionmentioning
confidence: 99%
“…The fibrin–agarose hydrogels used to fill the collagen conduits in the A‐FAH and C‐FAH groups were elaborated following previously described protocols (Carriel et al ., , ; Scionti et al ., ). The clinical outcomes and electrophysiological results obtained in each experimental group of animals have been described previously (Carriel et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…Se trata de un polímero natural biodegradable que participa de los procesos naturales de reparación tisular y que posee cadenas fibrilares largas que permiten flexibilidad y una elevada fuerza mecánica (29). Recientemente se ha descrito además que la unión de la fibrina con la agarosa, que es un extracto de alga marina, refuerza las propiedades mecánicas del conjunto y que regulando la hidratación y la presión el biomaterial formado puede adquirir, en un amplio espectro, las propiedades biomecánicas deseadas (9,14,30). Los constructos elaborados con fibrina agarosa y fibrobastos han demostrado asimismo una gran capacidad para constituir estromas artificiales biomiméticos para distintos tipos de tejidos y órganos (8,10,12,14,15,31).…”
Section: Discussionunclassified
“…Como agente inhibidor de la fibrinolisis del biomaterial utilizamos ácido tranexámico (Amchafibrín ® , Fides Ecofarma, Valencia, España) y Cl 2 Ca 1% (p/v) para inducir la polimerización del plasma y la conversión del fibrinógeno en fibrina. Se realiza el control microscópico de la elaboración del biomaterial mediante microscopía electrónica de barrido en un microscopio PHILIPS Quanta 200, siguiendo procedimientos estandarizados (9).…”
Section: Generación De Constructos Tisularesunclassified